Garimpos de Juína : entre história, relatos e memórias (1986-1994) - Santos, Julio César dos (2012)
The project Juína was executed by Development Company of Mato Grosso (CODEMAT), in Northwestern Mato Grosso began in the late 1970. The aim of the government was to attract workers from regions marked by agrarian conflicts and promote the occupation of this part of the state, through the supply of land at affordable prices. In mid-1980, the settlers of Juína had already concluded that the challenges were greater than initially anticipated. From 1986, the news of the existence of diamond mines attracted to the region, a crowd of men and women in search of "wealth". They were workers, with values, ideals and goals of distinct farmers. People who lived in Juína at the time of intense mining activity keep in their memories, experiences related to the activity, the daily prospecting in the villages, the diamond trade, the practices of violence and all that lived in an age of disillusionment of dreams. Some of these experiences are collective, other individuals, many of misfortune, suffering, and other losses of success. By oral sources, parts of these memoirs were turned into history. These reports were analyzed and compared with information from official records, bibliographic, journalistic and private archives. The social history was the main tool used in this work. The villages prospecting, especially the Garimpo Rice became dynamic environments of extreme precariousness, where prospectors and settlers lived in the same working conditions. Therefore, the meeting of the colonization process with the advent of "prospectors front" in the Northwestern part of Mato Grosso, gave a new impetus of occupation. The border was analyzed from the perspective of José de Souza Martins (2007) and conflicting relationships in optical Hannah Arendt (2009).